Dynamics of the plasma electrolytic polishing process of austenitic steel AISI 304 in a solution of ammonium sulfate - Mihal, O.V.; Moroz, O.V.; Starovoytov, R.I.; Lytovchenko, S.V.; Mazilin, B.A.; Iliushyn, L.O. (Вопросы атомной науки и техники, 2018)
Modern industrial technological processes together with scientific research activities require the special preparation of the metal surfaces for the further treatments. At present time the variety of techniques for the metal surface processing exist. Among them one could outline the plasma electrolytic polishing (PEP) due to its capability together with the decoration effect to enhance the surface properties. Despite the number of papers published in different journals the PEP stays an innovative surface treatment and requires further study to obtain optimal processing regimes. In present contribution the experimental study of PEP process dynamics with further numerical analysis of physical aspects for steel AISI 304 in a solution of ammonium sulfate with the mass fraction of 3% is given. After analyzing the experimental results the optimal PEP regime for the steel AISI 304 in a solution of ammonium sulfate with the mass fraction of 3% was identified.